ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA DITINJAU DARI PENGUASAAN MATERI PRASYARAT - Muhammad Rizal Usman; Kristiawati Kristiawati (Department of Mathematics Education, Universitas Kuningan, 2022)
This research aims to find out the level of mathematical literacy ability of students reviewed from the mastery of prerequisite materials, namely number material and changes and data. This research is a kualitati declututif study conducted in the final semester of 2021/2022, which is carried out offline in students of class VIII of State Junior High School 5 Makassar. Data collection techniques are carried out by test and interview methods. Data is analyzed using data condensation, data presentation, and conclusion withdrawal. Research instruments used in the form of tests of mathematical literacy skills. The results of the research from this study, the subjects of high material mastery as a whole answer the test problem correctly only difficulty using his reasoning in solving problems in problems, but many do the right application in answering literacy questions, but still somewhat lack in explaining mathematical concepts used in answering problems even though they have been written, Moreover, with the mastery of low material that really can not explain what mathematical concepts it uses in answering literacy questions. As for the recommendations of researchers, for future studies that want to conduct similar research should examine more broadly and develop the ability of mathematical literacy.